The impact of FDI on export performance: Empirical evidence from EU candidate countries - Bucevska, Vesna (International Statistical Institute (ISI), 2009)
In the last several years EU candidate countries (Croatia, Macedonia and Turkey) have been experiencing a constant growth of both exports and foreign direct investments. The growth of FDI flows to EU candidate countries partly reflects steps taken by those countries in the framework of market-oriented reform processes, often associated with EU accession. While there are numerous theoretical and empirical studies about the relationship between FDI and export performance, there are no studies treating this issue in the case of EU candidate countries as a group of countries. The objective of this paper is to bridge the gap by analyzing the relationship between FDI and export performance. In order to explore the main determinants of export performance and to provide econometric estimation of the direct as well as special effects of FDI on export, we use pooled data for the EU candidate countries in the period 1997-2006 and created an econometric model. The results of the estimated model, which show that FDI indeed have had a positive impact on export performance of all EU candidate countries, provide insightful information for the policy makers of these countries in the process of formulation of policies for attracting more FDI in the future.
Keywords: econometric model, FDI, export performance